The global burden, trends, and inequalities of individuals with developmental and intellectual disabilities attributable to iodine deficiency from 1990 to 2019 and its prediction up to 2030 - Yang, Xuesong; Liu, Cheng; Liu, Yanbo; He, Zhigang; Li, Juan; Li, Yijing; Wu, Yanqiong; Manyande, Anne; Feng, Maohui; Xiang, Hongbing (Frontiers in Nutrition, 2024)
Objective The objective of this study was to assess the global burden of disease for developmental and intellectual disabilities caused by iodine deficiency from 1990 to 2019. Methods Using data from the global burden of disease (GBD) 2019, we conducted a cross-country inequity analysis to examine the worldwide burden of developmental and intellectual disabilities caused by the issue of iodine deficiency from 1990 to 2019. Absolute and relative inequality were assessed by the slope index of inequality and the concentration index, respectively. After summarising the latest evidence, we also projected the age-standardized prevalence and years lived with disability (YLD) rates up to 2030 using the BAPC and INLA packages in R statistical software. Results In 2019, the global age-standardized prevalence and YLD rates for developmental and intellectual disabilities due to iodine deficiency were 22.54 per 100,000 population (95% UI 14.47 to 29.23) and 4.12 per 100,000 population (95% UI 2.25 to 6.4), respectively. From 1990 to 2019, the age-standardized prevalence and YLD rates of developmental and intellectual disabilities due to iodine deficiency decreased significantly. Geographic distribution showed that areas with lower socio-demographic indices (SDI) were the most affected. The correlation between higher SDI and lower prevalence highlights the role of economic and social factors in the prevalence of the disease. Cross-national inequity analysis shows that disparities persist despite improvements in health inequalities. In addition, projections suggest that the disease burden may decline until 2030. Conclusion This research underscores the necessity for targeted interventions, such as enhancing iodine supplementation and nutritional education, especially in areas with lower SDI. We aim to provide a foundation for policymakers further to research effective preventative and potential alternative treatment strategies.